Thermal Effect of ExternalCladding Materials on The Microclimate in Urban Environment - Al-Jawadi, Miqdad Haidar; Al-Tamimi, Ahmed Hani (Iraqi Journal of Architecture and Planning, 2018)
It has been found recently, that many architects are using new imported materials for external cladding, which might cause an increase in air temperature of the urban environment, and creating new microclimate thermally differ from other places according to the type of cladding materials used on building façade , especially in commercial streets, which is believed that most people feels changes in thermal difference in commercial streets more than the difference in residential districts, where people are usually indoors. So due to the lack of information about the effect of such material on urban environment, the paper aimed to contribute in discovering the effect of thermal reflectivity and emissivity of number of cladding materials commonly used by local designers, in order that designers can have useful information, so that they will be free to choose the proper and the best suitable materials. For getting better and more realistic results, an experimental model of a part of commercial street represents 8 three story buildings Scale 1:10 has been built on the roof of Department of Architecture, University of Technology , Baghdad, Iraq during August & September 2012. The selected scale model has been chosen because it is suitable for taking measurements with the available infra red image camera (Fluke Came Ti32), the electronic digital thermometers as well as the suitability for the available thickness of selected cladding materials The skeleton of the commercial street model has designed in a way that it can help in changing and testing easily any type of cladding material. The experiments for six common cladding materials, shows that the material with highest thermal effect on microclimate during day time is the white aluminum composite panels, and the least effect is by using ruff white cement rendering. It has to be pointed outher that usingthe experimental modelin this studyis closer to realitythanmathematical calculationseven when reducing the size ofthe model, due tothe fact thatmodel factor is influenceddirectly proportionalto the model scale, and because we could not find commercial streetswith uniform and similarcladding material. Key words: Sustainable urbanenvironment, climaticdesign, Cladding Materials, urban design